2023
DOI: 10.3390/horticulturae9111177
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Silver Nanoparticles in Response of In Vitro Boysenberry Plants to Drought Stress

Sevinç Şener,
Hülya Sayğı

Abstract: Drought is one of the leading abiotic factors limiting morphological and physiological activities in blackberry cultivation. In this study, the effects of silver nanoparticles (AgNPs) on some morphological and biochemical processes in boysenberry (Rubus ursinus Chamisso and Schlenhtendal) under drought stress were investigated. The experiment was performed with three drought stress levels simulated with Polyethylene Glycol (PEG) (0, 4, 8%) and three AgNP treatments (0, 0.1, 0.2 mg L−1) in vitro conditions. Dro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Silver nanoparticles, have been observed to increase the content of chlorophyll and to increase the rate of photosynthesis. 56 This helps the entire plant to grow and develop. Studies indicate that nanoparticulate application helps to regulate antioxidant enzymatic activity and maintains cellular water balance.…”
Section: Synthesis Of Nanofertilizermentioning
confidence: 99%
See 1 more Smart Citation
“…Silver nanoparticles, have been observed to increase the content of chlorophyll and to increase the rate of photosynthesis. 56 This helps the entire plant to grow and develop. Studies indicate that nanoparticulate application helps to regulate antioxidant enzymatic activity and maintains cellular water balance.…”
Section: Synthesis Of Nanofertilizermentioning
confidence: 99%
“…In addition, research has suggested that silver nanoparticles have the potential to provide resistance to drought stress in a variety of plant species. 56…”
Section: Synthesis Of Nanofertilizermentioning
confidence: 99%